PENGARUH PENERAPAN METODE PEMBELAJARAN BERMAIN PERAN TERHADAP HASIL BELAJAR BIOLOGI SISWA SMP KELAS VIII SMPN 24 PADANG - Hartisa, Febri; Nurhadi, Nurhadi; Fitriani, Vivi (Pendidikan Biologi, 2014)
ABSTRACTÂ This research is background by the low of outcomes student in biology class VIII of SMPN 24 Padang and haver minimal competencess of criterion (KKM) yet. The out comes of student are lowered by the teacher make of interesting teaching methods yet. This research intend how the influence of the aplication methods learning role playing for the study outcomes of students is biology at class VIII of SMPN 24 Padang. This kind of research is an eksperimental which using of the Randomized Control Group postest only design, the populations are all of student at class VIII of SMPN 24 Padang Â in periode of 2013/2014. The sampling by purposive sampling technical a sample he found by class VIIIB as eksperimental class and class VIIIC as control class. The instrument are make is written test in objective question. The data of analysis technical used uji ât by level Î± 0,05. The outcomes of data analysis Â is found a price t hitung 5,36, while t table 1,67. This is t arithmatic > t table. Therefore hiphotesis is accepted that the application of Â methods learning role playing for the study outcomes of student at class VIII of SMPN 24 Padang.Â